Recycling in Islamic Perspective Case Study of Architectural Works Using Waste Building Materials - Yolandita Aristawati; Hanif Budiman; Putu Ayu P. Agustiananda; Noram Irwan Ramli (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Waste is a serious environmental problem worldwide. Waste can refer to various types of materials or substances resulting from human, industrial, agricultural and other activities. The waste problem covers aspects such as management, environmental impact and human health. In this paper, an Islamic perspective on waste recycling in building architecture is discussed. Case studies involving architectural works with the use of building waste reflect the principle of recycling in practice. Waste buildings are materials or structures which have been retired for their original purpose but which still have the potential to be reused with little or no major alterations. Architectural works such as households, community facilities, or even commercial buildings can use used materials that are still usable to reduce demand for new resources. However, in implementing the recycling concept in architecture, it is necessary to pay attention to several aspects, such as structural safety, quality of used materials, and compatibility with the surrounding environment. Islam encourages the use of resources wisely and in moderation, as well as minimizing negative impacts on the environment. This is the responsibility of humans as caliphs on earth to preserve the environment and to maintain the balance of the ecosystem. as well as compatibility with the surrounding environment. Islam encourages the use of resources wisely and in moderation, as well as minimizing negative impacts on the environment. This is the responsibility of humans as caliphs on earth to preserve the environment and to maintain the balance of the ecosystem. as well as compatibility with the surrounding environment. Islam encourages the use of resources wisely and in moderation, as well as minimizing negative impacts on the environment. This is the responsibility of humans as caliphs on earth to preserve the environment and to maintain the balance of the ecosystem. Keywords: Islamic Perspective; Architecture; Recycle; Building material; Environmental Conservation